2020
DOI: 10.1101/2020.09.03.282111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative genomics ofClostridiumspecies associated with vacuum-packed meat spoilage

Abstract: Bacterial species belonging to the Clostridium genera have been recognized as causative agents of blown pack spoilage (BPS) in vacuum packed meat products. Whole-genome sequencing of six New Zealand psychrotolerant Clostridium isolates derived from three meat production animal types and their environments was performed to examine their roles in BPS. Comparative genome analyses have provided insight into the genomic diversity and physiology of these bacteria and divides Clostridia into two separate species clus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 58 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…In the present study, we broadened the analysis to encompass 34 CEC genomes, including five reference strains whose genomes were lacking. Similar to the previous study ( Palevich et al, 2021 ), the 96% ANI was sufficient to delineate all CEC species apart from C. estertheticum . Comparatively, the 70% dDDH for intraspecies delineation ( Meier-Kolthoff et al, 2013 ) also sufficed for all genomospecies apart from C. estertheticum .…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In the present study, we broadened the analysis to encompass 34 CEC genomes, including five reference strains whose genomes were lacking. Similar to the previous study ( Palevich et al, 2021 ), the 96% ANI was sufficient to delineate all CEC species apart from C. estertheticum . Comparatively, the 70% dDDH for intraspecies delineation ( Meier-Kolthoff et al, 2013 ) also sufficed for all genomospecies apart from C. estertheticum .…”
Section: Discussionsupporting
confidence: 79%
“…Comparative studies between ANI and DDH values show that ANI values of 95–96% are equivalent to the 70% DDH ( Goris et al, 2007 ; Richter and Rosselló-Móra, 2009 ). In this regard, a recent study used ANI of 96% to delineate six strains into distinct CEC species and showed the value was sufficient ( Palevich et al, 2021 ). In the present study, we broadened the analysis to encompass 34 CEC genomes, including five reference strains whose genomes were lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genomic DNA for metagenomic 16S rRNA gene amplicon sequencing of the V3-V4 hypervariable region was isolated from C. vicina pooled samples of 100 larvae as well as 10 entire adult males and females per replicate ( n =5 for each). High molecular weight genomic DNA was prepared using a modified phenol:chloroform protocol recently applied to difficult samples such as parasitic roundworms (7, 8), fastidious anaerobic rumen bacteria (911) and spore-forming psychrotolerant Clostridium isolated from spoiled meat (12, 13). A DNA library was prepared using the Illumina 16S V3-V4 rRNA library preparation method (Illumina, Inc., San Diego, CA) according to the manufacturer’s instructions (20), and sequenced on the Illumina MiSeq platform with the 2× 250 bp paired-end (PE) reagent kit v2 producing a total of 3,017,007 PE raw reads.…”
Section: Announcementmentioning
confidence: 99%